Interplay of chiral and helical states in a quantum spin hall insulator lateral junction - Calvo, M; de Juan, F; Ilan, R; Fox, E; Bestwick, A; Mühlbauer, M; Wang, J; Ames, C; Leubner, P; Brüne, C; Zhang, S; Buhmann, H; et al. (American Physical Society, 2017)
We study the electronic transport across an electrostatically gated lateral junction in a HgTe quantum well, a canonical 2D topological insulator, with and without an applied magnetic field. We control the carrier density inside and outside a junction region independently and hence tune the number and nature of 1D edge modes propagating in each of those regions. Outside the bulk gap, the magnetic field drives the system to the quantum Hall regime, and chiral states propagate at the edge. In this regime, we observe fractional plateaus that reflect the equilibration between 1D chiral modes across the junction. As the carrier density approaches zero in the central region and at moderate fields, we observe oscillations in the resistance that we attribute to Fabry-Perot interference in the helical states, enabled by the broken time reversal symmetry. At higher fields, those oscillations disappear, in agreement with the expected absence of helical states when band inversion is lifted.